Efektivitas Program Keluarga Harapan (PKH) Dalam Mendukung Pengentasan Kemiskinan Di Desa Mataindaha Kecamatan Pasikolaga Kabupaten Muna - Yunita, Rahma; Tarifu, La; Aminuddin, Aminuddin (Universitas Halu Oleo, 2020)
The purpose of this study is to describe the effectiveness of the Hope Family Program and find out what factors influence the Effectiveness of the Hope Family Program in the Mataindaha Village, Pasikolaga District, Muna Regency. Data collection techniques using observation, interviews, and documentation. The data analysis technique in this study was using descriptive qualitative analysis techniques. Informants in the study amounted to 8 (eight) people consisting Village Head, village secretary, PKH assistant and 5 (five) PKH recipient communities. The results of this study indicate that the Effectiveness of the Family Hope Program in Mataindaha Village in supporting poverty alleviation is ineffective as seen from the indicators put forward by Sutrisno namely Understanding the Program, Target, Timely, Achieving Goals and Real Change. Because PKH management in the field only meets 2 indicators, namely on time and real change. While understanding the program there are still PKH recipient communities who lack understanding of the objectives, benefits and allocation of PKH funds, then the accuracy of the targets is still not appropriate because there are still PKH recipient communities from families who are able, for the achievement of the objectives it cannot yet be fully effective. While the factors that hamper the effectiveness of the PKH Program are among them the incorrect targets that are not in accordance with the requirements or criteria for PKH recipients and the lack of coordination from the village government in relation to the management of PKH target data.